PENERAPAN STRATEGI GUIDED INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR SISWA AMBON KONSEP SISTEM PERNAPASAN MANUSIA KELAS XI SMA NEGERI 12 AMBON - Lodia Johanis (Program Studi Pendidikan Biologi FKIP Unpatti, 2015)
Background: The guided inquiry strategy is a set of learning activities that involves maximally all students' ability to search and investigate systematically, critically, logically, analytically, so that they are able to solve their own problems confidently. Based on the experience of researchers during the KKM in SMA Negeri 12 Ambon, it can be seen that most students have difficulty in biology learning process. It is commonly seen from very low student scores or not achieving KKM standards in the respiratory system material, whereas KKM specified in biology subjects especially class XI is 70. This is due to the teacher-centered learning process, where teachers who provide materials and students who heard. For that, researchers want to use guided inquiry strategy in this learning process, especially the concept of human respiratory system. Method: This type of research is qualitative with the aim to see the cognitive learning outcomes of the human respiratory system of the students of grade XI IPA of SMA Negeri 12 Ambon using Guided Inquiry strategy. This research was conducted in class XI SMA Negeri 12 Ambon District Nusaniwe Ambon city. The research procedure consists of several stages, namely: 1) Planning stage and 2) stage of research implementation. Before doing teaching and learning activities, researchers provide motivation to students about the respiratory system in humans. Then do a preliminary test to determine the initial ability of students. Students are divided into 5 groups and each group must fill the LKS already prepared by the researcher. Then the researchers began to apply guided inquiry strategy. Result: increasing number of students who get KKM 70 score in Biology subject, this is proven by the classification of mastery. Before the learning process (PBM), as many as 31 students of learning outcomes are not complete or get value under the KKM. After the teaching and learning activities are conducted by using the guided inquiry strategy of students whose learning outcomes are not complete or get the value under the KKM is reduced to 0 students. Conclusion: Learning biology with guided inquiry strategies can improve student learning outcomes XI IPA SMAN 12 Ambon